2020
DOI: 10.3906/sag-2002-126
|View full text |Cite
|
Sign up to set email alerts
|

Areclinicianssuccessful in diagnosingcutaneousadnexaltumors? aretrospective, clinicopathologicalstudy

Abstract: Background/aim: Cutaneous adnexal tumors (CAT) are rare tumors originating from the adnexal epithelial parts of the skin. Due to its clinical and histopathological characteristics comparable with other diseases, clinicians and pathologists experience difficulties in its diagnosis.We aimed to reveal the clinical and histopathological characteristics of the retrospectively screened cases and to compare the prediagnoses and histopathological diagnoses of clinicians. Materials and methods:The data of the last 5 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 33 publications
3
16
0
Order By: Relevance
“…The literature is summarized in Table S4 (see Supporting Information). 3,9, Our population had a significantly higher female representation (male to female ratio of 0Á77 : 1) than that found in the reported literature (male to female ratio of 0Á98 : 1) and had The age of our cohort of patients was older than that reported in the existing SAT literature. The method of ascertainment in our work aimed to include all SATs, and the selected case mix of tumours is likely to have contributed to the difference in age seen in our cohort.…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations
“…The literature is summarized in Table S4 (see Supporting Information). 3,9, Our population had a significantly higher female representation (male to female ratio of 0Á77 : 1) than that found in the reported literature (male to female ratio of 0Á98 : 1) and had The age of our cohort of patients was older than that reported in the existing SAT literature. The method of ascertainment in our work aimed to include all SATs, and the selected case mix of tumours is likely to have contributed to the difference in age seen in our cohort.…”
Section: Discussionmentioning
confidence: 48%
“…In a smaller study (n = 65 cases), 36Á4% of SATs were clinically unsuspected 9 and in another study (n = 528 cases) the clinical diagnosis was unsuspected in 51% of cases. 3 We found frequent discrepancies between the clinical and histological diagnosis in cases that were histologically diagnosed to be benign SATs, with a correct clinical diagnosis being provided only 28% of the time. SATs were not considered in the clinical differential in 41% of cases, with a further 16% of cases providing no attempt at diagnosis.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…The results showed that clinical prediagnoses and histopathological diagnoses were compatible in 45% of the 65 patients, while they were contradictory in 51%. The authors concluded that cutaneous adnexal tumors should be included in the differential diagnosis list, particularly in the presence of cutaneous papulonodular lesions without specific features and that a histopathological examination must be done in suspicious cases to reach a definitive diagnosis [1]. Here, we would like to shortly discuss the contribution of dermatoscopic examination to diagnostic accuracy in cutaneous adnexal tumors.…”
mentioning
confidence: 99%